ANALISIS PENDAPATAN PEDAGANG KAKI LIMA - Barkah, Zaenul Alam; Tewernusa, Ketysia Imelda; Bauw, Siti Aisah (Lensa Ekonomi, 2024)
This research aims to find out how much traders' income is and the influence of capital variables, working hours and length of business on the income of fresh vegetables traders in Wosi Village, Manokwari Regency. This type of research uses a descriptive quantitative approach. The population in this study were all fresh vegetables traders in Wosi Village, namely 40 traders, with a sample size of 40 respondents. Sampling used census techniques, namely by interviewing all respondents directly. The data source uses primary data in the form of a questionnaire and secondary data obtained from BPS, with the data analysis methods used, namely income analysis and multiple linear regression analysis. The results of this research show that the average income of fresh vegetables traders is IDR 11,816,350, the smallest income is IDR 3,664,000 and the largest income is IDR 54,270.00, with the partial working hours variable not having a significant effect on the trader's income. fresh vegetables, while the variables of capital and length of business partially have a significant effect on the income of fresh vegetables traders in Wosi Village.